2013
DOI: 10.1111/chf.12025
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Perfusion is Associated With White Matter Hyperintensities in Older Adults With Heart Failure

Abstract: Cognitive impairment is common in heart failure (HF) and believed to be the result of cerebral hypoperfusion and subsequent brain changes including white matter hyperintensities (WMH). The current study examined the association between cerebral blood flow and WMH in HF patients and the relationship of WMH to cognitive impairment. Sixty-nine patients with HF completed the mini mental state examination (MMSE), echocardiogram, transcranial Doppler sonography (TCD) for cerebral blood flow velocity of the middle ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
92
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 60 publications
2
92
0
1
Order By: Relevance
“…This ischemic mechanism has been demonstrated in animals 2,3 ; however, human studies studying the effect of lower CBF on development of WMHs and lacunes are scarce and cross-sectional. [4][5][6][7][8] A possible explanation for the lack of an association between baseline pCBF and progression of WMHs and lacunes could be that they represent different pathological processes. The development of WMHs and lacunes could be the result of mechanisms unrelated to hemodynamic processes, such as neurodegeneration and genetic predisposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ischemic mechanism has been demonstrated in animals 2,3 ; however, human studies studying the effect of lower CBF on development of WMHs and lacunes are scarce and cross-sectional. [4][5][6][7][8] A possible explanation for the lack of an association between baseline pCBF and progression of WMHs and lacunes could be that they represent different pathological processes. The development of WMHs and lacunes could be the result of mechanisms unrelated to hemodynamic processes, such as neurodegeneration and genetic predisposition.…”
Section: Discussionmentioning
confidence: 99%
“…1 Evidence supporting this mechanism comes from animal studies and cross-sectional studies in humans. [2][3][4][5][6][7][8] These studies showed that lower cerebral blood flow (CBF) is related to more WMHs and lacunes in the general population and in patients with cardiovascular disease. Also, patients with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) have significantly lower baseline CBF than controls.…”
mentioning
confidence: 99%
“…A few studies have evaluated the extent of brain changes in heart failure patients in comparison to non-heart failure patients. Alosco et al [5] described an association between cerebral hypoperfusion defined by transcranial Doppler sonography of the middle cerebral artery and greater white matter hyperintensities seen on brain MRI. Almeida et al [6] also studied brain changes over a 2 year span in heart failure patients and concluded with subtle regional gray matter loss.…”
Section: Introductionmentioning
confidence: 99%
“…2 Acute walking tests have also been shown to associate with cognitive function in a convenience sample of patients with chronic heart failure, 3 which is an important determination as cognitive dysfunction has been shown to occur among those with heart failure. 4,8 Thus, not only may the results of a 6MWT provide valuable information about cardiopulmonary functioning among heart failure patients, it may also help to provide useful information with regard to cognitive function, which ultimately may influence engagement in physical activity behavior. 9 Using a population-based sample, the purpose of this study was to improve our understanding of the potential relationship between the results of a short walking test and cognitive function among older adults with congestive heart failure.…”
mentioning
confidence: 99%